Plantas medicinais - Almeida, Mara Zélia de (EDUFBA, 2011)
Plantas Medicinais collaborates with the preservation and multiplication of information obtained in community works about the use of plants for medicinal purposes, with due respect to the traditions of African cultural heritage in medicine in Brazil. Traditional therapeutic indications indicate plants for medicinal purposes that go far beyond conventional therapy, assuming, at certain times, a mystical character, based on cultural beliefs inherent to the ethnic group. The view of man, as an integral being, respected in his moment of fragility, when some illness of psychic or somatic origin afflicts him, stands out as the main perspective for understanding this work.